Epidemiology of gout in Hong Kong: a population-based study from 2006 to 2016 - Tsoi, Man Fung; Chung, Man Ho; Cheung, Bernard Man Yung; Lau, Chak Sing; Cheung, Tommy Tsang (Arthritis research & therapy, 2020)
Objective To determine the incidence and prevalence of gout in the general population and the utilisation of urate-lowering therapy (ULT) among patients with gout in Hong Kong. Methods A total of 2,741,862 subjects who attended any outpatient clinics or accident and emergency department (with or without hospitalisation) in 2005 and did not die before 2006 were identified from the Clinical Data Analysis and Reporting System (CDARS) of the Hospital Authority in Hong Kong. All subjects were followed until the end of 2016 or death. Demographics, diagnosis of gout, serum urate levels, and ULT prescriptions were retrieved from CDARS. Gout was defined by the diagnosis codes in CDARS. The serum urate levels achieved after prescribing ULT were the means of all serum urate levels measured 6 months after prescriptions. Results were analysed by R version 3.3.3 with package ‘prevalence’ version 0.4.0. Results The crude incidence of gout increased from 113.05/100,000 person-years (PY) in 2006 to 211.62/100,000 PY in 2016. The crude prevalence of gout increased from 1.56% in 2006 to 2.92% in 2016. Only 25.55% of patients with gout were prescribed ULT in 2016. 35.8% of patients treated with ULT were able to achieve the target serum urate level of < 6 mg/dL. Conclusions Population ageing as well as other risk factors contributed to an increase in the incidence and prevalence of gout in Hong Kong. In 2016, the crude prevalence of gout in Hong Kong was comparable to that in many western countries. However, only one in four patients with gout in Hong Kong was prescribed ULT.